Social capital and health: a meta-analysis - Xue, Xindong; Reed, W. Robert; Menclova, Andrea (Journal of health economics, 2020)
The relationship between social capital and health has received extensive attention in fields such as public health, medicine, epidemiology, gerontology and other health-related disciplines. In contrast, the economics literature on this subject is relatively small. To address this research gap, we investigate the cross-disciplinary empirical literature using meta-analysis. We analyze 12,778 estimates from 470 studies. Our analysis finds that social capital is significantly related to a variety of positive health outcomes. However, the effect sizes are consistently very small. This finding is robust across different types of social capital (e.g., cognitive, structural, bonding, bridging, linking), and for many different measures of health outcomes (e.g., mortality, disease/illnesses, depression). The small effects that we estimate cast doubt on recent initiatives to promote health through social capital such as those by the WHO, the OECD, and US Healthy People 2020.